RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI PUTIH (Brassica pekinensis L.) TERHADAP PEMBERIAN BERBAGAI DOSIS PUPUK KANDANG SAPI - Elsafiana, Elsafiana; Mahfudz, Mahfudz; Wahyudi, Imam (AGROTEKBIS, 2017)
This research aims to study the influence of cow manure on the growth and yield of chinese cabbage. This research is compiled using a randomized block design with seven treatment consists of one level ie dosing cow manure, without the provision of cow manure, a dose of 10 ton ha-1,Â Â a dose of 20 ton ha-1, a dose of 30 ton ha-1, dose 40 t ha-1, a dose of 50 t ha-1 doses of 60 ton ha-1. Each unit treatment was repeated three times so that there are 21 experimental units. The observed variables include plant height, leaf number and weight of the crop in a plots. The results showed that treatment of cattle manure at a dose of 60 ton ha-1 (equivalent to 25.92 kg plot-1) gives better results than other treatments on observations of plant height, leaf number and weight of the crop.Key Words: Chinese Cabbage, cow manure.